1999
DOI: 10.1074/jbc.274.49.34523
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Recognition of Collagen-specific Molecular Chaperone HSP47

Abstract: Prior to secretion, procollagen molecules are correctly folded to triple helices in the endoplasmic reticulum (ER). HSP47 specifically associates with procollagen in the ER during its folding and/or modification processes and is thought to function as a collagen-specific molecular chaperone (Nagata, K. (1996) Trends Biochem. Sci. 21, 23-26). However, structural requirements for substrate recognition and regulation of the binding have not yet been elucidated. Here, we show that a typical collagen model sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 31 publications
5
54
1
1
Order By: Relevance
“…4a); this is much weaker than that previously recorded using a comparable fluorescence-based assay for Hsp47 binding to collagen (K d of 140 nM) (39). These results for collagen are in disagreement with Koide and coworkers (20) who have determined K d values (300 -1100 nM) for the interaction between mrmHsp47 and full-length type I-IV collagen using surface plasmon resonance. It seems more reasonable to compare our results with McDonald and Bä chinger (39) as our methodologies are identical.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…4a); this is much weaker than that previously recorded using a comparable fluorescence-based assay for Hsp47 binding to collagen (K d of 140 nM) (39). These results for collagen are in disagreement with Koide and coworkers (20) who have determined K d values (300 -1100 nM) for the interaction between mrmHsp47 and full-length type I-IV collagen using surface plasmon resonance. It seems more reasonable to compare our results with McDonald and Bä chinger (39) as our methodologies are identical.…”
Section: Resultscontrasting
confidence: 56%
“…Furthermore, recent work by Tasab and co-workers (16) has demonstrated that Hsp47 will bind to fully formed helical trimers in vivo, perhaps thereby stabilizing the triple helix and preventing chain dissociations. This functional hypothesis is supported by a recent demonstration that Hsp47 binds specifically to stretches of non-hydroxylated Pro-Gly-X repeats (20), regions of low structural stability within the full-length collagen triple helices. After binding there is clear evidence that triple helical procollagen-Hsp47 complexes are eventually transported from the endoplasmic reticulum to cis-Golgi (21), where Hsp47 is dissociated and recycled back to the endoplasmic reticulum (18).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…S100A4 [19], also known as fibroblast-specific protein 1 (FSP1) [20,21], is a member of the S100 superfamily of EF-hand calcium-binding proteins. P4HD is an essential enzyme for the biosynthesis of procollagen [22] and HSP47 is an ER-resident stress protein that is believed to function as a molecular chaperone specific to the biosynthesis of procollagen [23,24]. We identified the co-expressions of these profibrotic molecules within the atrial endocardial cells, suggesting transition to fibroblast phenotype.…”
Section: Endmt Process In Afmentioning
confidence: 93%
“…27 8C instead of 43 8C in the fully hydroxylated form. Type I procollagen molecules synthesized when the enzyme is inhibited by iron chelators are stored in the ER but can be hydroxylated and secreted if the Koide et al 1999). If correct, this provides one part of the solution to the problem of maintaining the long proa chains in a favourable conformation until the carboxyterminal propeptide, the locus of chain^chain interaction, is synthesized and released.…”
Section: Initial Assembly Of the Procollagen Moleculementioning
confidence: 99%